Japanese capitals in historical perspective : place, power and memory in Kyoto, Edo and Tokyo - Fiévé, Nicolas; Waley, Paul (RoutledgeCurzon, 2003)
Japan's ability to develop its own brand of modernity has often been attributed in part to the sophistication of its cities. Concentrating on Kyoto, Edo and Tokyo, the contributors to this volume weave together the links between past and future, memory and vision, symbol and structure, between marginality and power, and between Japan's two great capital cities.